Using magic trick problem-based activities to improve engagement in a listening class - Ikhsanudin Ikhsanudin; Sudarsono Sudarsono; Urai Salam (UPT Bahasa Universitas Tanjungpura, 2019)
Students engagement is a critical topic in the discussion of teaching and learning process quality, including at a tertiary level. The goal of this classroom action research is improving English education department engagement in a listening class through magic tricks problem-based activities. This research was conducted at the College of Teacher-Training and Education of Universitas Tanjungpura (FKIP UNTAN), Pontianak – Indonesia, in October-November 2018. The research was conducted in two cycles and the data were collected through participant observation. In three stages of analysis (initial coding, focused coding, and explanation), this research successfully improved the students' engagement. The students’ engagement was improved substantially in the second cycle after the magic trick activities were combined with pair discussion, group discussion, and cross-group discussion. The magic trick problem-based activities was an important factor that could invite the students' intellectual engagement. Whereas, the discussion activities improved the students emotional and behavioral engagement. The creative variation in the discussion stage had improved the students' engagement considerably.